From Fear to Fluency: The Case of Indonesian English Language Learners (ELLs) - Pasuhuk, Jennifer; Flores, Kathleen (12th International Scholars Conference 2025, 2026)
This study explores English-speaking anxiety among Indonesian English Language Learners (ELLs) particularly those studying abroad, with the goal of understanding how they overcome this challenge and achieve fluency. The research was carried out to address the persistent issue of speaking anxiety, which hinders language development and academic participation for many Indonesian learners. A qualitative case study approach was used which involved in-depth interviews among 14 Indonesian ELLs staying and studying in the Philippines. The findings revealed that learners experienced anxiety through physical symptoms, emotional conflict, and social pressures. These struggles were often triggered by low language proficiency, fear of making mistakes, lack of confidence, and fear of judgment especially in formal settings, spontaneous speaking tasks, and conversations with native speakers and even among fellow Indonesians. To cope with these challenges, participants used internal strategies such as relaxation techniques, increased exposure to English, positive mindset adjustments, and committed learning efforts. They also relied on external strategies, like peer support, encouragement from teachers, and prayer. These combined efforts helped learners build speaking confidence and gradually reduce anxiety. The study recommends individualized coping strategies, supportive and inclusive teaching, culturally sensitive practices, and further research on long-term impacts of the coping strategies. This study contributes to a better understanding of English-speaking anxiety in the Indonesian context and offers insights for supporting learners in their journey from fear to fluency.